O NORTE BRASILEIRO NARRADO: passeios dramatúrgicos e identitários por uma região sub-representada pela telenovela (Comunicação & Inovação, 2022)
We propose that the choices of telenovela sceneries highlight power relations and inter-regional inequalities in Brazil, since certain regions, holders of a media and sociocultural hegemony, use to be more fictionally represented than others. In this context, we draw attention to an under-representation of the North, since, in the two first decades of this century, only three telenovelas from Rede Globo were set in the region. Considering this under-representation, we seek to understand how the works explore and conceive the North in identity terms.
Keywords: comunicacations and consumption; sociocultural identities; telenovela